Motion Graphic-Based Work and Energy Physic Learning Media Development - Zulkarnain Zulkarnain; Islahudin Islahudin; Nuryanti Tul Zahrah (Jurnal Educatio FKIP UNMA, 2023)
Physic learning usually requires more observation to form certain knowledge and concepts. Physic does not only consist of a collection of various knowledge or facts that can be memorized, but also consists of an active process of using the mind in studying natural phenomena that cannot be explained. Physics subject is one of the keys to success in increasing the ability to adapt to change and enter the world of technology. Therefore, certain ways are needed to convey the material in science lessons, especially physics. This study aims to produce Motion Graphic-based Work and Energy Learning Media on feasible work and energy materials in terms of materials, media, and students' responses. The research method used is research and development (R&D), using the 4D model (Define, Design, Develop, and Disseminate). The subjects were conducted in class X IPA 1, which consisted of 15 students. The instrument used is a questionnaire. The results showed that media could be used as a teaching media in the physics subject of work and energy based on expert judgment with very good categories for media, materials, and students' responses. So it can be concluded that Work and Energy motion graphic media can be employed as a ground-breaking teaching tool for engaging Work and Energy physic material.